The Risk Management And Usage Of The Net Present Value-At-Risk To Evaluate Indonesian Toll Road - Natasha Evelyn Saragih; Dewi Hanggraeni (UNIVED Press, 2024)
This study evaluates the financial feasibility and risk management of toll road infrastructure so as characteristics of toll road projects prone to risks and uncertainties. The study was conducted using case study and qualitative methods. The parameters used to determine the fair value of the project through parameters such as NPV, IRR, Payback Period, NPV at risk, and Risk Adjusted Return on Capital (RAROC) for financial and risk-based feasibility evaluation. This study also conducted a risk assessment in risk management analysis. The study provides various illustrations of possible outputs (NPV) and risk variability so that it can provide a more communicative and varied offer and recommendation, especially for investors as a consideration in making investment decisions. The results of the risk assesment process showed a low to the very high-risk level that requires different treatment. This study contributes understanding the investment in Indonesia toll road project